Research on Disaster Prevention and Control Technology for Directional Hydraulic Fracturing and Roof Plate Unloading - Dong Liu; Jiayue Deng; Tao Yang; Jie Zhang; Haifei Lin; Hui Liu; Jiarui Sun; Yiming Zhang (Applied Sciences)
In coal seam groups where the spacing between the upper and lower seams is small, the lower seam working face is significantly influenced by residual coal pillars from the upper seam and the void spaces created during mining. This presents considerable challenges for underground mining safety. Through field investigations, the layout of the coal seam quarry above the working face of the 3−1 coal seam in Yanghuopan Mine was examined, along with the distribution of the residual coal pillars. This allowed for the identification of the interlayer rock strata characteristics. Subsequently, we analyzed the mechanism of directional hydraulic fracturing and decompression to determine the key parameters of the 3−1 coal seam. Using the Rock Fracture Process Analysis 3D (RFPA 3D) numerical simulation, we evaluated the effects of various factors on the initiation and propagation of hydraulic fracturing-induced cracks, formulated the evolution law of these fractures, and incorporated the damage variables into the analysis. Additionally, we assessed the influence of different parameters on crack initiation and extension during hydraulic fracturing, using RFPA 3D simulations to derive the evolution law governing directional hydraulic fractures. This allowed us to define the hydraulic fracturing parameters for the 3−1 interbedded rock layers by integrating the process parameter calculations with the damage variables. Based on these findings, an on-site implementation plan was developed and executed, followed by a comprehensive evaluation of the construction results. The study concludes that directional hydraulic fracturing and decompression effectively contribute to the prevention and control of roof-related disasters in the mining of lower coal seams where seam spacing is minimal. This research offers valuable theoretical insights and practical reference for disaster prevention and control in similar geological conditions.